Economic, Legal, and Political Dimensions of Competition / Lectures in Economics Theory, Institutions, Policy - Demsetz Harold (North Holland Publishing Company, 1991)
The Presumption of Competition, Competition in the Private Sector, Competition in the Public Sector, The Growth of Government.